Congenital Anomalies of The Kidney and Urinary Tract A single center study - Al Ubaidy, Mohamed Saad (Karbala Journal of Medicine, 2021)
Background: Congenital anomalies of the kidney and urinary tract (CAKUT) are a major cause of morbidity and collectively represent a significant cause of chronic kidney disease (CKD) in children and young adults; they cover a wide scope of malformations that result from a defect in the morphogenesis that occur at the level of the kidney, collecting system, ureter, bladder, or urethra, It is important to diagnose these anomalies early enough and initiate therapy to minimize renal damage, prevent or delay the onset of end stage renal disease (ESRD), and provide supportive care to avoid complications. Aim of study: To review the types, presentations, and methods of diagnosis of the CAKUT cases, attended the central teaching hospital of pediatrics. Patients & methods: A Cross-sectional study, conducted during the period from June 2017 to December 2017 in the nephrology department of the central teaching hospital of pediatrics in Baghdad/Iraq, where medical records of all patients who were diagnosed with CAKUT during the period from January 2007 to December 2016, were reviewed and analyzed in relation to patient demographics, clinical presentation, investigations, types of anomalies which were further subdivided to obstructive and non-obstructive and the difference between them. Results: Total of (308) patients records were collected and analyzed. The highest proportion of patients aged less than one year (43.8%) at the time of diagnosis. There were (64%) male and (36%) female. The highest proportion of patients had vesicoureteric reflux (VUR) (44.5%), followed by pelviureteric junction obstruction (PUJO). 26 patients (8.4%) had combined anomalies. The highest proportion of patients who had combined anomalies presented with PUJO and VUR (23.1%). Skeletal anomalies represented the most common extra-renal anomaly (4.2%). About half of the patients presented with urinary tract infection (UTI) (50.6%). Abdominal U/S was used in all patients to diagnose the pathology, followed by voiding cystouretherogaphy (VCUG). There were 149 patients (48.4%) had elevated Blood urea at the time of diagnosis, while 63 patients (20.5%) had elevated Serum creatinine. In Comparison between obstructive and non-obstructive anomalies, the highest proportion of obstructive anomalies were diagnosed in the age group below one year (63%), and we had a significant association (P=0.001). The highest proportion of obstructive anomalies was seen among male patients (80.2%) and there is a significant association (P=0.001). The highest proportion of obstructive anomalies was seen among patients presented with UTI (65.4%) and there is a significant association (P=0.001). (11.1%) of patients with non-obstructive anomalies presented with failure to thrive (FTT), there was a significant association (P=0.019). Means of Blood urea and Serum creatinine were higher among patients with non-obstructive anomalies than patients with obstructive anomalies and these differences were extremely statistically significant. (P = 0.0001). Conclusion: Most of the patients diagnosed with CAKUT were males, aged less than one year. VUR was the most common anomaly, followed by PUJO. UTI was the most common presentation and skeletal anomalies were the most common extra-renal anomaly. Obstructive renal anomalies were most common in male patients, less than one year of age and UTI was significantly more common in obstructive anomalies in comparison with non-obstructive cases in which FTT was significantly more common.